Orthotopic liver transplantation at Groote Schuur Hospital : a serial analysis of biliary cytokines and biochemical parameters - Spearman, C W N (Department of Medicine, 2017)
Orthotopic liver transplantation is the treatment of choice for many patients with end-stage liver disease. Despite advances in immunosuppression, acute rejection remains common (up to 70%) and results in significant patient morbidity. It is frequently difficult to distinguish abnormal liver function due to rejection from that due to infection, biliary obstruction or ischaemic injury without performing invasive procedures such as a liver biopsy or angiography which may be Clinically, the diagnosis of rejection is usually once the immunological process is already hazardous. made late, established. In this study, we evaluated standard biochemical parameters and cytokine concentrations (IL-1, IL-6 and TNF-alpha) in serial samples of bile obtained post-operatively via the Ttubes of patients following orthotopic liver transplantation in order to determine whether there are any biochemical or immunological pointers to the early diagnosis of rejection which would enable earlier administration of appropriate antirejection therapy. Biliary cytokines did not prove to be useful and reliable markers of early rejection. Serial measurement of biliary bilirubin levels showed an early and significant decrease a few days prior to rejection, and were a more sensitive marker of graft function than serum bilirubin levels.